Filmes de diamante não-dopados e dopados: um estudo sistemático usando espectroscopia Raman - Silva, William Fortunato da (Universidade Federal de São Carlos, 2004)
Diamond films grown by both hot filament (HFCVD) and microwave-plasma (MW-CVD) assisted chemical vapor deposition were investigated. Raman spectroscopy, scan- ning electron microscopy and X-ray di¤raction were employed in order to perform systematic studies about the crystalline quality and the phase purity of the films, as a function of the deposition temperature. It was found that both techniques produced diamond films of similarly good purity; however, the MWCVD produced films of higher crystalline quality. Changes in the shape of the Raman line were found to be due to both phonon confinement and residual stress. Photoluminescence (PL) measurements were employed in a detailed study of the origin of defects in the diamond films grown by MWCVD and HFCVD. The results showed evidence of optical centers induced by different impurities. The defects were captured by silicon and tungsten atoms incorporated, respectively, in the diamond lattice of films grown by MWCVD and HFCVD. Boron-doped diamond films were also studied using Raman and transport measurements. Boron incorporation induces disorder in the diamond structure, causes the appearance of a band observed at ~ 1220 cm-1, and provokes an effect in the Raman line of diamond that could be attributed to the Fano type interference. Resistivity as a function of the boron concentration - in association with the Raman spectra - and temperature dependent transport measurements were employed. The results showed that the variable range hopping mechanism (VRH) dominates the transport in these doped diamond films.
Keywords: Física da matéria condensada; Caracterização ótica; Sólidos - propriedades óticas; Deposição por vapor químico (CVC); Raman, Espectroscopia de; Semicondutores; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA